(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2012)
In the first part of the article the concept servant leadership is investigated from a Christian reformational perspective. Several characteristics of servant leadership are presented. A pilot narrative investigation was also done on the perceptions of twelve novice educators regarding leadership, with reference also to servant leadership. The findings of this study are presented in the second part of the article. Meaningful correlations are indicated between the findings of the literature study and the narrative investigation.